A sense of injustice loosens the moral bind of law: specifying the links between procedural injustice, neutralizations, and offending - McLean, Kyle (Criminal justice and behavior, 2016)
Existing literature demonstrates a clear connection between perceptions of procedural injustice and offending behaviors. Despite this connection, the mechanisms through which procedural injustice influences offending remain theoretically underdeveloped. To address this gap, the current study proposes that techniques of neutralization can be used to further develop our understanding of the connection between procedural injustice and criminal behavior. Using longitudinal data from the Gang Resistance Education and Training (GREAT) program, the links between procedural injustice, techniques of neutralization, and offending are explored. Results show that the effect of procedural injustice on offending is partially mediated by individuals? neutralization attitudes. This finding expands the scope of procedural justice theory by demonstrating that procedural injustice is associated with attitudes conducive to criminal behavior rather than only the behavior itself.